Implementation of Activity Based Costing (ABC) Method for Industry in Indonesia: Literature Review - Tri Aprianto; Indra Setiawan; Bambang Setiawan; Fikri Al Latif (Proceeding Mercu Buana Conference on Industrial Engineering, 2019)
Activity Based Costing (ABC) is an accounting method that identifies and assigns costs to overhead activities and then assigns these costs to products. The purpose of this paper is to provide an assessment of 20 articles on ABC method in the Indonesian region published during the period 2017 to 2020. This ABC model is used to allocate all costs, based on the resources used to carry out product-related activities. and services provided to customers. This paper contains the results of many different aspects. These aspects include industry focus, total distribution focus and publication year focus. This paper is useful for all types of industrial sectors to identify and determine costs for all company activities. This paper also provides benefits for future researchers to add insight and reference for studies related to ABC method.